Intention vs. Perception of Designed Atmospheres in Fashion Stores - Mia Borch Münster (Copenhagen Business School (CBS), 2018)
Retail stores are designed to attract and inspire consumers. They also function as communication platforms between brand and consumer. Customers, both consciously and unconsciously, decode messages embedded in the store design, and use them in their decision-making. But how can design managers know with any certainty whether the choices they make actually add value, to the products in the store? This dilemma has been addressed from varying perspectives in businessrelated design and marketing literature. John Heskett (2005) acknowledges the conflict of imperatives that obtains between a company and the users of its products and ascribes to design the role of providing a bridge between them. Philip Kotler (1973) underscores the need for designers to understand the targeted consumers by making a distinction between intended and perceived atmosphere. The intended atmosphere is, of course, the set of sensory qualities that the designer of an environment means to invoke. But a design is not always perceived as intended; indeed, perception can vary significantly from one customer to the next. Apart from offering insights in the retail designer's process of creating stores that function as a marketing tool, this dissertation proposes a method for measuring whether decisions made by the store designer do indeed support the products from the targeted consumer's perspective. In four articles, a toolbox is provided, offering insights of four types: (1) the theoretical and empirical, aimed at developing an understanding of the different categories within the retail designer's working process; (2) a codification of the stakeholders and constraint generators affecting the retail design process; (3) the proposal of a new method for studying spillover effects from store interior to product; and (4) the testing of this method in two field experiments, where we measure the effects of retail design on those for whom the design is ultimately intended: consumers.
hdl:10398/9624
Keywords: 650